Bladder drainage options for people with spinal cord injury: A Mini-Review - Julia Patrick Engkasan; Chua Li Shun; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Neurogenic bladder is one of the negative consequences following a spinal cord injury (SCI). SCI patients who have neurogenic bladder depend on alternative methods to drain urine from their bladder. These include indwelling catheters, reflex voiding , suprapubic tapping and intermittent catheterisation. This review summarizes evidence from the literature of five selected complications (renal failure, urinary tract infections, calculi, urethral stricture, and bladder cancer) that could result from use of the different bladder drainage methods. There is inconsistent evidence to support the superiority of intermittent over indwelling catheterisation on risk of renal impairment, urethral stricture, and renal calculi. Indwelling catheterisations are associated with higher risk of bladder calculi and cancer. Caution needs to be taken when interpreting this review, as many of its findings are from retrospective studies, and more than a decade old. Clinicians need to communicate the evidence to their patients when making the decision on method of bladder drainage. Keywords: Rehabilitation Catheterisation Incontinence Urology Paraplegia Renal failure.